Microfinance: Viable Approaches for Islamic Banking Implementation - Wan Noor Hazlina Wan Jusoh; Anita Md. Shariff (Global Review of Islamic Economics and Business, 2015)
Islamic banks have very much engaged in debt financing businesses the same way and as much as their conventional counterparts do.  Debt financing businesses, as widely implemented, were specifically targeted for and tailored to the needs of middle and upper income group of people.  The low income people remain left out and forgotten in most banking businesses while microfinance instruments, which are meant to help the poor and needy, remain unpopular among the banking institutions. There is indeed increasing calls for Islamic banks to seriously consider this type of instrument as part of their religious obligation embedded under their Islamic identity. This paper demonstrated that microfinance instruments are viable for Islamic banks to consider despite the claims that the contracts are less secured and hence, too risky to embark in.   A number of microfinance instruments based on Islamic concepts namely Musyarakah, Murabahah, Mudharabah, Ijarah and Qard al-Hassan as well as operational frameworks such as SPV and wakalah, were being proposed and discussed to pave ways for its implementation by the Islamic banks.